Impact of Corporate Governance on Financial Performance of Nifty 50 Companies : An Empirical Analysis - Jose, Amala Maria; Jose, Meenu Treesa; G., Suresh (Indian Journal of Research in Capital Markets, 2022)
This paper attempted to study the impact of corporate governance guidelines on the financial performance of the NIFTY 50 companies. The CG score of each company was calculated to know its impact on financial parameters. Correlation and regression analysis on the data collected highlighted that corporate governance had no significant impact on the profitability of the companies. It was also found that the existing set of laws did not significantly impact the performance of companies. Therefore, the policymakers were advised to make the laws more stringent so that the CG guidelines by the statute shall be followed by every company resulting in their better performance. Furthermore, the study proposed an increased focus on practices that, in turn, would enhance the sustainability of a business.